If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * 2 + 3x + 5 = x * 2 + -1x + 4 Reorder the terms for easier multiplication: 2x + 3x + 5 = x * 2 + -1x + 4 Reorder the terms: 5 + 2x + 3x = x * 2 + -1x + 4 Combine like terms: 2x + 3x = 5x 5 + 5x = x * 2 + -1x + 4 Reorder the terms for easier multiplication: 5 + 5x = 2x + -1x + 4 Reorder the terms: 5 + 5x = 4 + 2x + -1x Combine like terms: 2x + -1x = 1x 5 + 5x = 4 + 1x Solving 5 + 5x = 4 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 5 + 5x + -1x = 4 + 1x + -1x Combine like terms: 5x + -1x = 4x 5 + 4x = 4 + 1x + -1x Combine like terms: 1x + -1x = 0 5 + 4x = 4 + 0 5 + 4x = 4 Add '-5' to each side of the equation. 5 + -5 + 4x = 4 + -5 Combine like terms: 5 + -5 = 0 0 + 4x = 4 + -5 4x = 4 + -5 Combine like terms: 4 + -5 = -1 4x = -1 Divide each side by '4'. x = -0.25 Simplifying x = -0.25
| 3*x+(x-10)=200 | | 10=-2x-x+7 | | y=100(0.78)3x | | 10(2y+2)-y=2(8y-2) | | 0.88+0.16(10-x)=0.40x | | 6-x-1=6-(x+1) | | 7-4x-2x=-35 | | (-4x)+(-3x)+x= | | 5c-1=34 | | -(-6y-3z+6)= | | (x^4)-4(x^3)+7=0 | | .08x=13-0.5x | | 4k(k+1)=25 | | -4x-6+5x=-10 | | (3x+9)-16=-5 | | 29=4x-7 | | 6x=-2x-2 | | (3x+9)-16=5 | | 11y+1.9= | | 20a^5b^3+30a^3b^2-40a^2b^3= | | 10+6x-2x=50 | | -4t-2+7t=4 | | -4x-8=8x+16 | | 4(x+14)= | | 5.6=-1+x | | 5x+1+5x=-99 | | 7x-1=9x-6 | | 5x-2(5+2x)=3+x-8 | | bx-6x=4a-ax | | -(6y-3z+6)= | | x^2+2mx-(m-20)=0 | | 2(3x+y)=(2x+5y) |